Generalized 𝜶-𝝍 Contractive Type Mappings and Related Fixed Point Theorems with Applications - Erdal Karapınar; Bessem Samet (Abstract and Applied Analysis)
We establish fixed point theorems for a new class of contractive mappings. As consequences of our main results, we obtain fixed point theorems on metric spaces endowed with a partial order and fixed point theorems for cyclic contractive mappings. Various examples are presented to illustrate our obtained results.